Penerapan Evidence Based Nursing Progresive Muscle Relaxation Terhadap Kecemasan Pada Pasien Pre Operasi Fraktur Ektremitas - Sahrudi; Masfuri; Waluyo, Agung (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Surgery is experience can anxiety. One of management extremity fractures is surgery with internal fixation inscrews, wires, and plates. The purpose this study to apply and prove effectiveness of Progressive MuscleRelaxation (PMR) in reducing patient anxiety in orthopedic treatment room at Fatmawati Hospital Jakarta.EBN (Evidence Based Nursing) this study using PICO model which was carried out on 8 patients withPreoperative Extremity Fractures. Anxiety levels using the State Trait Anxiety Inventory (STAI) instrument.The results of implementation evidence based nursing obtained an average anxiety score before PMR was64.25 with a standard deviation of 4.027. Meanwhile, the average anxiety score for PMR was 47.75 with astandard deviation of 3.955. The results of statistical analysis showed significant results, namely the value of p= 0.001. Every action taken must be based on the available evidence so as to improve the quality of service, soit is suggested that PMR can be used as a non-pharmacological intervention for nurses to help reduce patientanxiety.